2019
DOI: 10.3389/fmicb.2019.02540
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TGEV Miller Strain Infection Effect of Lactobacillus plantarum Supernatant Based on the JAK-STAT1 Signaling Pathway

Abstract: Transmissible gastroenteritis (TGE), caused by transmissible gastroenteritis virus (TGEV), is one many gastrointestinal inflections in piglets, characterized by diarrhea, and high mortality. Probiotics are ubiquitous bacteria in animal intestines, which have many functions, such as promoting intestinal peristalsis and maintaining the intestinal balance. We found that the supernatant of the Lp-1 strain of Lactobacillus plantarum, isolated in our laboratory, and named Lp-1s had marked anti-TGEV effect on IPEC-J2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…Evidence for antiviral activity of probiotic strains against common respiratory viruses, including influenza, rhinovirus, and respiratory syncytial virus comes from clinical and experimental studies (17)(18)(19)41). While none of these effects or mechanisms have been tested on the new SARS-CoV-2 virus, this should not negate considering this approach, especially when effects of probiotics against other coronavirus strains have been reported (42)(43)(44)(45). Furthermore, patients are dying from secondary bacterial infections.…”
Section: Mechanistic Basis For the Action Of Probiotics To Prevent Inmentioning
confidence: 99%
“…Evidence for antiviral activity of probiotic strains against common respiratory viruses, including influenza, rhinovirus, and respiratory syncytial virus comes from clinical and experimental studies (17)(18)(19)41). While none of these effects or mechanisms have been tested on the new SARS-CoV-2 virus, this should not negate considering this approach, especially when effects of probiotics against other coronavirus strains have been reported (42)(43)(44)(45). Furthermore, patients are dying from secondary bacterial infections.…”
Section: Mechanistic Basis For the Action Of Probiotics To Prevent Inmentioning
confidence: 99%
“…The authors also reported that the E. faecium alters the expression of interleukins, IL-6, and IL-8 and induces the production of Nitric oxide which might be the reason for its antiviral activity (Chai et al 2012). The study of Wang et al (2019) also reported the antiviral activity of Lactobacillus plantarum against transmissible gastroenteritis virus, which in turn activates the antiviral proteins via JAK-STAT signalling pathway and up-regulate the expression of interferon genes, resulting in anti-transmissible gastroenteritis virus activity (Wang et al 2019). These reports further indicate the efficacy of probiotic strains to treat the infection of coronavirus.…”
Section: Role Of Probiotics In Respiratory Virus Infectionsmentioning
confidence: 99%
“…Additionally, it has been noted that the SARS-CoV-2 also uses the same ACE2 receptor for the attachment of the virus to the host cell, which was previously used by the SARS-CoV. A single mutation in the spike proteins of SARS-CoV-2 may have considerably increased its attachment affinity for ACE2 4,5 .…”
Section: Genomic Variations Of Sars-cov-2mentioning
confidence: 99%
“…As studies from China have shown, COVID-19 may be accompanying intestinal dysbacteriosis, thereby causing severe infection; restoration of gut homeostasis may be helped through probiotic strains. It is reasonable that probiotic strains, when orally administered, could stimulate gut-lung association and some strains can migrate from the gut to other nearer sites, like breast, to medicate mastitis 4 . The microbiota of the gut has a significant effect on the host immune response, systemically, and on immune reactions at nearby mucosal sites, such as lung.…”
Section: Mechanism Of Action Of Probiotics To Prevent Covid-19mentioning
confidence: 99%
See 1 more Smart Citation